2014
DOI: 10.1136/jclinpath-2014-202349
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 antagonist inhibits perineural invasion of adenoid cystic carcinoma

Abstract: CXCR4 is associated with perineural invasion in ACC. AMD3100, which can effectively diminish perineural invasion of ACC, may have an adjuvant role in the management of ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…). CXCR4 has been heavily linked to an increasingly invasive phenotype in a variety of cancers types; however, many of the studies have looked at CXCR4 invasion in only a 2D setting (Guo et al ., ; Jeong et al ., ; Niu et al ., ; Xu et al ., ; Ying et al ., ). To our knowledge, this is the first experimental evidence of miR‐9 knockdown inducing an invasive phenotype via CXCR4 in 3D culture.…”
Section: Discussionmentioning
confidence: 99%
“…). CXCR4 has been heavily linked to an increasingly invasive phenotype in a variety of cancers types; however, many of the studies have looked at CXCR4 invasion in only a 2D setting (Guo et al ., ; Jeong et al ., ; Niu et al ., ; Xu et al ., ; Ying et al ., ). To our knowledge, this is the first experimental evidence of miR‐9 knockdown inducing an invasive phenotype via CXCR4 in 3D culture.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CXCR4 and PNI has also been noted in pancreatic cancer (Jiang, Li, Sun, Zhao, & Zhou, 2014). Lastly, Jeong et al showed that CXCR4 was expressed in the regions surrounding the areas of PNI in adenoid cystic carcinoma samples (Jeong et al, 2014). In the same study, it was reported that administering AMD31000 in a murine PNI model reduced the incidence of PNI from 71.4% to 18.8%.…”
Section: Other Potential Players: Ncam and Cxcr4mentioning
confidence: 79%
“…Of note, in each of these trials it not possible to determine whether the observed effect was due to inhibition of RET or alternatively Flk-1 (the VEGF receptor) as SU5416 targets both. Lastly, as previously mentioned, AMD3100 (plerixafor) a CXCR4 inhibitor, has been shown inhibit PNI in mouse models of adenoid cystic carcinoma (Jeong et al, 2014). Plerixafor is better known for its use in mobilizing hematopoietic stem cells into the peripheral circulation in cancer patients (Uy, Rettig, & Cashen, 2008) although CXCR4's potential association with poor prognosis in melanomas suggests targeting this receptor may be worth investigating in melanomas.…”
Section: Clinical Potential Of Neurotrophins As Therapeutic Targetsmentioning
confidence: 96%
“…Also, AMD3100 has the anti-angiogenic efficacy that is associated with a reduction of tumor growth and invasiveness in orthotopic glioblastoma xenotransplanted rats (Ali et al, 2013). In another study, the clinical relevance of CXCR4 neutralization with siRNA or AMD3100 in chondrosarcoma and adenoid cystic carcinoma (ACC) were investigated and the results indicated a decreased tumor growth and metastasis dissemination (Jeong et al, 2014). AMD3100 is used as a cell mobilizing drug in stem cell therapy and also has an anti-HIV potential for AIDS patients (De Clercq, 2015).…”
Section: Amd3100mentioning
confidence: 99%